Enhancing the inhibition of dental erosion and abrasion with quercetin-encapsulated hollow mesoporous silica nanocomposites - Chen, Jia-Min; Cheng, Yi-Ling; Yang, Meng-Hui; Su, Chen; Yu, Hao (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Dental erosion and abrasion pose significant clinical challenges, often leading to exposed dentinal tubules and dentine demineralization. The aim of this study was to analyse the efficacy of quercetin-encapsulated hollow mesoporous silica nanocomposites (Q@HMSNs) on the prevention of dentine erosion and abrasion. Method: Q@HMSNs were synthesized, characterized, and evaluated for their biocompatibility. A total of 130 dentine specimens (2 mm × 2 mm × 2 mm) were prepared and randomly distributed into 5 treatment groups (n = 26): DW (deionized water, negative control), NaF (12.3 mg/mL sodium fluoride, positive control), Q (300 μg/mL quercetin), HMSN (5.0 mg/mL HMSNs), and Q@HMSN (5.0 mg/mL Q@HMSNs). All groups were submitted to in vitro erosive (4 cycles/d) and abrasive (2 cycles/d) challenges for 7 days. The specimens in the DW, NaF, and Q groups were immersed in the respective solutions for 2 min, while treatment was performed for 30 s in the HMSN and Q@HMSN groups. Subsequently, the specimens were subjected to additional daily erosion/abrasion cycles for another 7 days. The effects of the materials on dentinal tubule occlusion and demineralized organic matrix (DOM) preservation were examined by scanning electron microscopy (SEM). The penetration depth of rhodamine B fluorescein into the etched dentine was assessed using confocal laser scanning microscopy (CLSM). The erosive dentine loss (EDL) and release of type I collagen telopeptide (ICTP) were measured. The data were analysed by one-way analysis of variance (ANOVA) with post hoc Tukey’s test (α = 0.05). Results: Q@HMSNs were successfully synthesized and showed minimal toxicity to human dental pulp stem cells (HDPSCs) and gingival fibroblasts (HGFs). Q@HMSNs effectively occluded the dentinal tubules, resulting in a thicker DOM in the Q@HMSN group. The CLSM images showed more superficial penetration in the HMSN and Q@HMSN groups than in the quercetin, NaF, and DW groups. The Q@HMSN group exhibited a significantly lower EDL and reduced ICTP levels compared to the other groups (p < 0.05). Conclusion: Q@HMSNs hold promise for inhibiting dentine erosion and abrasion by promoting tubule occlusion and DOM preservation.